Tightening and anti-wrinkle gel composition with barrier repairing effect and preparation method of firming and anti-wrinkle gel composition

By crosslinking carboxymethyl chitosan and rosemary acid and electrospinning to form a highly absorbent matrix material, combining biologically active peptides and animal placenta proteins, the problem of poor water absorption of traditional facial mask materials is solved and the efficiency of the essence is achieved Absorption and sustained release significantly improve the firming and anti-wrinkle effect of the skin.

CN119280104APending Publication Date: 2025-01-10ZHONGKE RUNHANG HEALTH TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411452180.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The poor water absorption of traditional facial mask materials leads to the incomplete absorption of essence, serious waste, low utilization rate of active substances, and difficult to achieve sustained release effect, affecting the skin's anti-aging effect.

Method used

Carboxymethyl chitosan and rosemary acid cross-link to form a water-absorbent gel matrix, and electrospinned with water-soluble modified polysaccharides to form a matrix material with high water absorption and breathability, combined with specific biologically active peptides Gel compositions with ingredients such as animal placenta proteins to promote penetration and sustained release of essence.

Benefits of technology

It significantly improves the absorption efficiency of the essence, reduces waste, enhances the skin's firming and anti-wrinkle effect, improves the penetration of skin care ingredients, and achieves the effect of barrier repair, making the skin firm, anti-wrinkle and light lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005089465030000071
    Figure BDA0005089465030000071
  • Figure BDA0005089465030000081
    Figure BDA0005089465030000081
  • Figure BDA0005089465030000111
    Figure BDA0005089465030000111
Patent Text Reader

Abstract

The invention particularly discloses a firming and anti-wrinkle gel composition with a barrier repairing effect and a preparation method of the firming and anti-wrinkle gel composition. The gel composition is formed by soaking a matrix material in essence, the matrix material is obtained by cross-linking carboxymethyl chitosan and rosmarinic acid to form a water-absorbing gel matrix, mixing the water-absorbing gel matrix with water-soluble modified polysaccharide and then carrying out electrostatic spinning; the essence comprises the following components: animal placenta protein, bioactive peptide, hydrogenated castor oil, vitamin E, glycosylglycerol and the like. The gel composition has high water absorption and air permeability, and the absorption efficiency of essence can be remarkably improved; meanwhile, the stability of bioactive components in the storage process and the slow-release effect of the bioactive components in the use process can be improved, efficient permeation is achieved, then the barrier repairing effect is achieved, and skin aging is delayed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cosmetics, and more specifically, to a firming and anti-wrinkle gel composition with barrier repairing effect and a preparation method thereof. Background Art

[0002] As consumers continue to accumulate skin care knowledge and pursue beauty, the demand for anti-aging skin care products, as one of the important categories of daily skin care, will continue to increase. Consumers' demand for skin care products is not limited to basic hydration and moisturizing. They also hope that the products can have the effects of deep nourishment, repairing damaged skin, and fading fine lines. Anti-aging skin care products usually contain a variety of anti-aging ingredients, such as collagen, hyaluronic acid, vitamin C, etc., which aim to slow down skin aging by replenishing the nutrients needed by the skin and improving the elasticity and firmness of the skin.

[0003] Taking facial masks as an example, the common anti-aging products on the market currently mainly use traditional mask cloth materials, combined with essence containing active substances, and absorb them into the skin through facial application. Although this method can supplement nutrition for the skin to a certain extent, it has problems such as low absorption rate and low utilization rate of active substances. At the same time, some existing facial masks have poor user experience, such as heavy stickiness, airtightness, and skin tightness after use.

[0004] For example, Chinese patent CN 110974755A discloses a natural anti-aging facial mask and its preparation method and application, which includes mask paper and mask liquid, and the mask liquid includes the following components: sargassum polypeptide, trehalose, sodium hyaluronate, clove extract, grape extract, green tea extract, papaya extract, rose essential oil, and sterile deionized water. It is formed by mixing the above substances to form an essence, and then placing it in a bag containing mask paper or mask cloth. This mask paper or mask cloth has poor water absorption and cannot fully absorb the essence. When used, the essence often remains in the bag and is not completely absorbed, causing waste; the essence will also drip during facial application, which is neither convenient nor hygienic; at the same time, the active ingredients in the essence are always in a free state, and it is difficult to achieve a sustained release effect during the facial application, which reduces the penetration effect of the active substances in the essence on the skin, especially the poor transdermal absorption effect of the biological macromolecular active substances, and it is difficult to fully exert its anti-aging effect.

[0005] In view of this, in order to solve the above-mentioned problems, this application is specially proposed. Summary of the invention

[0006] In order to solve the technical problems that the poor water absorption of traditional matrix materials leads to the waste of essence due to incomplete absorption, and the active substances cannot be effectively utilized, the present application provides a firming and anti-wrinkle gel composition with barrier repair effect and a preparation method thereof. The gel composition has the effects of moisturizing, locking water and sustained release, can promote the permeability of active ingredients, and then play a barrier repair role, making the skin firm and anti-wrinkle and lightening lines.

[0007] This application provides the following technical solutions:

[0008] In one aspect, the present application provides a firming and anti-wrinkle gel composition with barrier repairing effect, which is formed by soaking a matrix material in an essence;

[0009] The matrix material is obtained by cross-linking carboxymethyl chitosan and rosmarinic acid to form a water-absorbing gel matrix, and then mixing the water-absorbing gel matrix with a water-soluble modified polysaccharide and performing electrostatic spinning;

[0010] The essence comprises: 0.5-3.5wt% of animal placenta protein, 0.3-1.5wt% of bioactive peptides, 0.5-3% of hydrogenated castor oil, 0.1-4% of vitamin E, 0.2-0.5% of glycerol glucoside, 1-5% of glycerol, 0.1-4% of hyaluronic acid, 0.5-0.7% of carbomer, 0.01-0.05% of arginine, 0.1-1% of phenoxyethanol, 0.01-0.5% of EDTA-2Na, and the balance is deionized water.

[0011] Further, the above-mentioned bioactive peptide includes at least one of PEP-129, PEP-383 and PEP-518;

[0012] The amino acid sequence of PEP-129 is: Leu-Asp-Glu-Glu-Asn-Gly-Glu-Leu;

[0013] The amino acid sequence of PEP-518 is: Gly-Asp-Pro-Glu-Arg-Phe-Tyr-Cys;

[0014] The amino acid sequence of PEP-383 is: Cys-Leu-Gln-Pro-Glu-Thr-Gly-Glu-Tyr-Arg-Cys.

[0015] In the above technical scheme, three bioactive peptides are provided. These three active peptides are obtained by the inventor team through the construction of a high-throughput screening model for Nrf2 agonists. They can effectively promote the proliferation of human umbilical cord mesenchymal stem cells and restore the proliferation vitality of aged human umbilical cord mesenchymal stem cells. At the same time, the active peptide also has a good effect of inhibiting fibroblasts and human immortalized keratinocytes from ultraviolet damage, and has excellent photorepair performance for photodamaged cells. Sharing it with animal placental protein can, on the one hand, effectively promote animal placental protein to scavenge free radicals, protect cells from oxidative damage and light damage, thereby slowing down the aging of the skin; on the other hand, it can act as an active factor together with animal placental protein to promote the synthesis of skin collagen and elastic fibers, thereby reducing the appearance of wrinkles and fine lines, making the skin tighter and smoother.

[0016] Furthermore, the preparation method of the above matrix material comprises:

[0017] (1) mixing carboxymethyl chitosan, rosmarinic acid and water, and crosslinking at 135-145° C. for 2-5 hours to obtain a water-absorbing gel matrix;

[0018] (2) The water-absorbent gel matrix is ​​mixed with the water-soluble modified polysaccharide and water to form a spinning solution, and the spinning solution is subjected to electrostatic spinning to obtain a matrix material.

[0019] In the above technical scheme, the selection of cross-linking temperature and cross-linking time will greatly affect the water absorption of the gel matrix. By determining the optimal combination of cross-linking temperature and time, a gel matrix with a moderate degree of cross-linking is obtained to facilitate further electrospinning with water-soluble modified polysaccharides, thereby avoiding excessive cross-linking, which may easily cause agglomeration, broken wires, holes, etc. during electrospinning, thereby affecting the performance of the gel composition.

[0020] Furthermore, the water-soluble modified polysaccharide is obtained by blending and modifying pullulan and bletilla striata polysaccharide in a mass ratio of 8-10:1.

[0021] In the above technical scheme, a water-soluble modified polysaccharide mainly composed of pullulan and supplemented by bletilla striata polysaccharide is selected for electrostatic spinning. Pullulan has excellent water solubility and can form a uniform spinning solution in an aqueous solution. At the same time, pullulan also has a high water absorption capacity. By electrostatic spinning with a water-absorbing gel matrix, the resulting nanofiber membrane performs well in terms of retaining moisture and maintaining wetness. However, since the spinning solution formed by the water-absorbing gel matrix and pullulan is prone to coagulation and precipitation during the electrostatic spinning process, affecting the continuity of the spinning process and the stability of the fiber, a small amount of bletilla striata polysaccharide is added to the technical scheme. The interaction between bletilla striata polysaccharide and pullulan polysaccharide will change the viscosity and surface tension of the spinning solution, reduce the gelation and precipitation phenomena during the spinning process, and thus improve the continuity of the spinning process and the stability of the fiber.

[0022] Furthermore, the mass ratio of the water-absorbent gel matrix to the water-soluble modified polysaccharide is 1:5-7, and the concentration of the spinning solution is 15-17%.

[0023] In the above technical solution, the amount of water-absorbent gel matrix added will affect the stability of the spinning solution. In order to ensure that the matrix material has excellent water absorption performance and electrospinning stability, the mass ratio of the water-absorbent gel matrix to the water-soluble modified polysaccharide and the concentration of the spinning solution are limited.

[0024] Furthermore, in the process of preparing the water-absorbing gel matrix, the mass ratio of the carboxymethyl chitosan to rosmarinic acid is 450-550:1; the mass volume ratio of the carboxymethyl chitosan to water is (0.9-1.1):20.

[0025] In the above technical solution, the mass ratio of carboxymethyl chitosan to rosmarinic acid affects the degree of cross-linking reaction. If the amount of rosmarinic acid is too little, it is difficult to form an effective cross-linked network structure with carboxymethyl chitosan, resulting in poor water absorption of the matrix material; if the amount of rosmarinic acid is too large, it will lead to excessive cross-linking with carboxymethyl chitosan, and the obtained water-absorbing gel matrix will be hard and difficult to dissolve, making it difficult to perform electrospinning.

[0026] Furthermore, in the above electrospinning process, the spinning voltage is 28-30 KV, the receiving distance is 22-24 cm, and the extrusion rate is 0.4-0.6 ml / h.

[0027] In the above technical solution, various parameters of the electrospinning process are optimized to ensure that the electrospinning can proceed smoothly and obtain a nanofiber membrane with a smooth, uniform and fine surface.

[0028] In a second aspect, the present application also provides a method for preparing the gel composition according to any one of claims 1 to 7, comprising the following steps:

[0029] Disperse glycerin, hyaluronic acid and EDTA-2Na into deionized water, then add vitamin E, glyceryl glucoside, hydrogenated castor oil, bioactive peptides and animal placenta protein, heat and dissolve, add arginine to adjust the pH to 5.5-6.5, finally add carbomer and phenoxyethanol, filter and obtain an essence;

[0030] The essence solution is mixed with the matrix material and sterilized.

[0031] Furthermore, the mass volume ratio of the matrix material to the essence is 4-6:25.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. The firming and anti-wrinkle gel composition with barrier repairing effect provided by the present application is a matrix material prepared by a special process. The matrix material is obtained by cross-linking carboxymethyl chitosan and rosmarinic acid to form a water-absorbing gel matrix; and then mixing it with a water-soluble modified polysaccharide and electrostatic spinning. Among them, rosmarinic acid is a natural antioxidant, which also has anti-inflammatory and antibacterial effects. When it is mixed with carboxymethyl chitosan at high temperature, the hydroxyl and carboxyl groups in the rosmarinic acid molecules can undergo esterification and etherification reactions with carboxymethyl chitosan to form a cross-linked network structure. This cross-linked network structure makes the matrix material highly water-absorbent and breathable, thereby ensuring that the matrix material is light and thin while greatly increasing its water absorption and water-locking ability, which can significantly improve the absorption efficiency of the essence and reduce the waste of the essence during use. At the same time, because the matrix material has excellent water-locking ability, it can maintain the wetness of the composition during use, thereby improving the penetration of the skin care ingredients in the composition to the skin, and then playing a barrier repair role, making the skin firm and anti-wrinkle.

[0034] 2. Based on improving the water absorption of the matrix material, this application further develops a gel composition product containing specific bioactive peptides and animal placental proteins. By effectively fusing bioactive peptides and animal placental proteins with hydrogenated castor oil, vitamin E and glycerol glucoside, and then using them with a highly water-absorbent matrix material, the bioactive substances can be embedded in the cross-linked network structure of the matrix material, which can improve the stability of the active components during storage and the sustained release effect during use, thereby achieving efficient penetration and further improving the barrier repair effect of the product.

[0035] 3. In the essence of the gel composition, animal placenta protein is a natural bioactive substance extracted from animal placenta, which contains immunoglobulin, polypeptide, gonadotropin, prolactin, lysozyme, polysaccharide, urokinase and other ingredients. These ingredients give animal placenta protein good biological activity and multiple functions, such as anti-oxidation, anti-aging, growth promotion, and immunity enhancement. The use of bioactive peptides together with animal placenta protein can effectively promote the ability of animal placenta protein to scavenge free radicals, protect cells from oxidative damage and light damage, and thus slow down skin aging.

[0036] 4. In the essence of the gel composition, glycerol glucoside is the main active ingredient of resurrection grass (Milo), and after adding glycerol glucoside, it can promote the regeneration of filaggrin, which is further processed into amino acids in the upper epidermal stratum corneum to help the skin retain moisture and is an indispensable protein in the formation of the skin barrier. Thus, the barrier repair effect of the gel composition can be further enhanced. Hydrogenated castor oil has moisturizing and nourishing effects. After addition, it can soothe the skin and reduce the irritation of bioactive peptides and animal placental proteins to certain sensitive skins; vitamin E has an antioxidant effect, and using it together with bioactive peptides can synergistically improve the stability of bioactive peptides. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present application provides the effects of different matrix materials on the transdermal absorption rate of bioactive polypeptides in the essence. DETAILED DESCRIPTION

[0038] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0039] The bioactive peptides in this embodiment are obtained by the inventor team through the construction of a high-throughput screening model for Nrf2 agonists. The screening method is the same as that in CN 117964694A. The inhibitory effects of each peptide on Keap1 are shown in Table 1:

[0040] Table 1. High-throughput screening results

[0041]

[0042]

[0043] As shown in Table 1, compared with the positive small molecule reference ginsenoside Rg1, several sample peptides obtained by high-throughput screening have a good inhibitory effect on Keap1. This suggests that these peptides can be used to promote the proliferation of umbilical cord mesenchymal stem cells and are also expected to be used in cosmetics that inhibit aging.

[0044] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0045] Example of preparation of raw materials

[0046] Preparation Example 1

[0047] This preparation example provides a matrix material, and the preparation method thereof comprises the following steps:

[0048] (1) 50 g of carboxymethyl chitosan was added to 1 L of water, and after stirring to dissolve, 0.1 g of rosmarinic acid was added. The mixed solution was placed at 140° C. for cross-linking for 4 h. After the reaction was completed, the water-absorbing gel matrix was filtered;

[0049] (2) 90 g of pullulan and 10 g of bletilla striata polysaccharide were mixed and dissolved in water to obtain a water-soluble modified polysaccharide solution;

[0050] (3) adding the absorbent gel matrix (20 g) obtained in step (1) to the above water-soluble modified polysaccharide solution, heating to 55° C., stirring and dispersing at a speed of 1000 rpm, and adjusting the concentration of the obtained solution to 16% by adding water to obtain a spinning solution;

[0051] (4) Adding the spinning solution into an electrospinning device for electrospinning, the device parameters are as follows: spinning voltage is 28 KV, receiving distance is 23 cm, extrusion rate is 0.5 ml / h, and finally the matrix material is obtained.

[0052] Preparation Example 2

[0053] This preparation example provides a matrix material, and the preparation method thereof comprises the following steps:

[0054] (1) 45 g of carboxymethyl chitosan was added to 1 L of water, and after stirring to dissolve, 0.1 g of rosmarinic acid was added. The mixed solution was placed at 145° C. for cross-linking for 2 h. After the reaction was completed, the water-absorbing gel matrix was filtered;

[0055] (2) 80 g of pullulan and 10 g of bletilla striata polysaccharide were mixed and dissolved in water to obtain a water-soluble modified polysaccharide solution;

[0056] (3) adding the absorbent gel matrix (18 g) obtained in step (1) to the water-soluble modified polysaccharide solution, heating to 55° C., stirring and dispersing at a speed of 1000 rpm, and adjusting the concentration of the obtained solution to 17% by adding water to obtain a spinning solution;

[0057] (4) Adding the spinning solution into an electrospinning device for electrospinning, the device parameters are as follows: spinning voltage is 30 KV, receiving distance is 24 cm, extrusion rate is 0.4 ml / h, and finally the matrix material is obtained.

[0058] Preparation Example 3

[0059] This preparation example provides a matrix material, and the preparation method thereof comprises the following steps:

[0060] (1) 55 g of carboxymethyl chitosan was added to 1 L of water, and after stirring to dissolve, 0.1 g of rosmarinic acid was added. The mixed solution was placed at 135° C. for crosslinking for 5 h. After the reaction was completed, the water-absorbing gel matrix was filtered;

[0061] (2) mixing 100 g of pullulan and 10 g of bletilla striata polysaccharide, and dissolving them in water to obtain a water-soluble modified polysaccharide solution;

[0062] (3) adding the absorbent gel matrix (16 g) obtained in step (1) to the above water-soluble modified polysaccharide solution, heating to 55° C., stirring and dispersing at a speed of 1000 rpm, and adjusting the concentration of the obtained solution to 15% by adding water to obtain a spinning solution;

[0063] (4) Adding the spinning solution into an electrospinning device for electrospinning, the device parameters are as follows: spinning voltage is 28 KV, receiving distance is 22 cm, extrusion rate is 0.6 ml / h, and finally the matrix material is obtained.

[0064] Comparative Preparation Examples 4-9

[0065] This group of preparation examples is consistent with Example 1, except that:

[0066] Preparation Example 4: When preparing a water-absorbent gel matrix, the ratio of carboxymethyl chitosan: rosmarinic acid: water is 30 g: 0.1 g: 1000 ml;

[0067] Preparation Example 5: When preparing a water-absorbent gel matrix, the ratio of carboxymethyl chitosan: rosmarinic acid: water is 70 g: 0.1 g: 1000 ml;

[0068] Preparation Example 6: When preparing the spinning solution, the water-soluble modified polysaccharide is 100 g of pullulan, that is, no bletilla striata polysaccharide is added;

[0069] Preparation Example 7: When preparing the spinning solution, no water-absorbing gel matrix is ​​added, and pullulan and bletilla striata polysaccharide are mixed in a mass ratio of 90:10;

[0070] Preparation Example 8: When preparing the spinning solution, the weight ratio of the water-soluble modified polysaccharide to the water-absorbent gel matrix is ​​100 g:10 g;

[0071] Preparation Example 9: When preparing the spinning solution, the mass ratio of the water-soluble modified polysaccharide to the water-absorbent gel matrix is ​​100 g:30 g.

[0072] Example

[0073] This embodiment provides a firming and anti-wrinkle gel composition with barrier repairing effect, and the preparation method thereof is as follows:

[0074] (1) Prepare the materials according to the proportions in Table 2 below;

[0075] (2) dispersing glycerol, hyaluronic acid and EDTA-2Na into deionized water, then adding vitamin E, glyceryl glucoside, hydrogenated castor oil, bioactive peptides and animal placenta protein, heating and dissolving, adding arginine to adjust the pH to 5.5-6.5, and finally adding carbomer and phenoxyethanol, filtering, and obtaining an essence;

[0076] (3) The matrix material obtained in Preparation Example 1 was cut into facial shapes, each weighing 5 g, and placed in a packaging bag. 25 ml of the above essence was added, and the product was sterilized and packaged.

[0077] Table 2. Essence composition ratio

[0078]

[0079] The first group of comparison

[0080] The difference between this comparative example and Example 1 is that different matrix materials are used, and the components and proportions of the combined essence are consistent with those of Example 1:

[0081] Comparative Example 1: Using commercially available silk mask material paper as the matrix material;

[0082] Comparative Example 2: Using the matrix material provided in Preparation Example 4;

[0083] Comparative Example 3: Using the matrix material provided in Preparation Example 5;

[0084] Comparative Example 4: Using the matrix material provided in Preparation Example 6;

[0085] Comparative Example 5: Using the matrix material provided in Preparation Example 7;

[0086] Comparative Example 6: Using the matrix material provided in Preparation Example 8;

[0087] Comparative Example 7: The matrix material provided in Preparation Example 9 was used.

[0088] Experimental Example 1

[0089] This experiment investigates the water absorption and surface properties of different matrix materials

[0090] 5 g of the matrix material was placed in the essence and stirred in a constant temperature magnetic stirring device at 35°C and 200 r / min. After stirring for 20 min, the matrix material was filtered. The matrix material after water absorption was weighed, the swelling rate was calculated, and the matrix material was placed on pig skin for 30 min to observe the state of the composition. The results are shown in Table 3:

[0091] Table 3. Swelling test results

[0092]

[0093] As can be seen from Table 3, the matrix material provided in Example 1 of the present application has a swelling rate of up to 8 times, and after 30min, the film body is still smooth and flat, moist and full, does not drip, and does not dry the state of the film. Compared with the silk mask material of Comparative Example 1, the swelling rate performance is excellent. At the same time, although the matrix material obtained by Comparative Examples 2-6 shows a certain swelling rate, its water retention capacity is poor, and it is easy to dry the film after 30min of veneer, and part of it shows that the surface of the film body is uneven and has holes. Especially in Comparative Example 4, holes appear on the surface of the film body, and the quality is poor. It is mainly because pullulan polysaccharide is mixed with a water-absorbing gel matrix for electrostatic spinning, and the spinning solution is easily precipitated and caused by uneven spinning. And Comparative Example 7, due to the excessive content of the water-absorbing gel matrix in the spinning solution, the viscosity of the spinning solution is too large, and it is difficult to perform electrostatic spinning film formation.

[0094] Experimental Example 2

[0095] This experiment investigates the sustained release of bioactive substances in serum by different matrix materials.

[0096] The transdermal absorption rate was determined using a Franz transdermal absorption diffusion cell. The commercially available fragrant pig skin was fixed between the upper and lower chambers of the Franz transdermal absorption diffusion cell, with the stratum corneum facing upward. The gel composition provided in Example 1 and Comparative Example 1 (25 ml of essence) was applied to the fragrant pig skin. The test was performed using an RT800 automatic sampling transdermal diffusion system. Physiological saline was placed in the receiving cell, and the receiving solution was just in contact with the dermis. Subsequently, 100 μL was taken at 10 min, 20 min, 30 min, and 40 min, respectively. The concentration of PEP-518 in the receiving solution was detected using HPLC-MS, the transdermal absorption amount was calculated, and the transdermal absorption rate was calculated according to the following formula:

[0097] Transdermal absorption rate (%) = (transdermal absorption amount / initial dose) × 100

[0098] The results are as follows Figure 1 As shown, compared with Comparative Example 1, the transdermal absorption rate of the gel composition provided in Example 1 of the present application is weaker in the first 10 minutes, but as time goes by, the transdermal absorption rate gradually increases, showing a sustained release effect, and the final transdermal absorption rate is greater than that of Comparative Example 1.

[0099] The second group of comparison

[0100] The difference between this comparative example and Example 1 is that the bioactive peptides used are different, and the other components and contents are the same;

[0101] Comparative Example 8: The bioactive peptide is glutathione;

[0102] Comparative Example 9: The bioactive peptide is PEP-150, and its amino acid sequence is: Cys-Leu-Asp-Pro-Gly-Thr-Gly-Glu-Tyr-Leu-Cys;

[0103] Comparative Example 10: The bioactive peptide is PEP-449, and its amino acid sequence is: Leu-Asp-Pro-Glu-Asp-Gly-Pro-Phe-Leu;

[0104] Comparative Example 11: The bioactive peptide is PEP-520, and its amino acid sequence is: Gly-Asp-Thr-Pro-Glu-Gly-Tyr-Cys.

[0105] Performance testing

[0106] The following photoaging resistance test and skin elasticity test were performed on Example 1 and Comparative Example 1 and Comparative Examples 8-11:

[0107] 1. Antioxidant damage test

[0108] DPPH free radical scavenging rate test method: Take 10 mg of DPPH, dissolve it in ethanol, and dilute it to obtain a 10ug / mL DPPH solution. Dilute 20 ml of the essence in the gel composition provided in Examples 1, 4 and 5, and Comparative Examples 1, 8-11 by 5 times with 70% ethanol to prepare the sample solution to be tested.

[0109] Do, Da and Dr were determined according to the following sample addition methods;

[0110] Add 2.5mL of DPPH solution and 1.5mL of ethanol to the test tube in sequence, let it stand for 20 minutes, and use a spectrophotometer to measure the absorbance at a wavelength of 517nm in a 1CM cuvette, which is recorded as D0; add 2.5mL of diluted DPPH solution and 1.5mL of the prepared sample solution to the test tube, mix well and let it stand for 20 minutes, and then use a spectrophotometer to measure the absorbance at a wavelength of 517nm, which is recorded as Da; add 2.5mL of ethanol and 1.5mL of the prepared sample solution to the test tube, mix well and let it stand for 20 minutes, and then use a spectrophotometer to measure the absorbance at a wavelength of 517nm, and the measured value is recorded as Dr;

[0111] The DPPH free radical scavenging rate was calculated according to the following formula and the results are recorded in Table 4.

[0112] Elimination rate = [1-(Da-Dr) / Do]*100

[0113] Table 4. Antioxidant damage test results

[0114] Test Group DPPH free radical scavenging rate Example 1 63.41% Example 4 66.23% Example 5 61.15% Comparative Example 8 48.56% Comparative Example 9 37.18% Comparative Example 10 39.45% Comparative Example 11 35.09%

[0115] As can be seen from Table 4, the essence of the gel composition provided by Examples 1, 4 and 5 of the present application has a more significant scavenging effect on DPPH free radicals, with a free radical scavenging rate of up to 66.23%. The free radical scavenging rate of Comparative Example 8 is only 48.56%, which shows that although glutathione has a good antioxidant effect, when it is used in combination with animal placental protein, the degree of synergistic effect of the antioxidant effect finally presented by the product is weaker than that of the active biological polypeptide of the present application. The free radical scavenging rate of Comparative Examples 9-11 is also significantly weaker than that of Examples 1, 4 and 5, which shows that: although these polypeptides all show a good inhibitory effect on Keap1 in the aforementioned high-throughput screening, when they are used in combination with animal placental protein, the antioxidant damage effect shown by the final product is still related to the specific amino acid sequence.

[0116] 2. Skin elasticity test

[0117] 40 healthy female volunteers aged 35-45 were selected and randomly divided into groups, with 10 people in each group. The gel composition was applied to the side wall 4 times a week, with an interval of 1 day between each application, for 4 consecutive weeks.

[0118] Skin elasticity test: Cutometer MPA580 was used to test the skin condition at week 0 and week 4 respectively. The test site was the right side wall. The probe was used to measure the same test area 3 times and the average value was taken.

[0119] The test results of skin elasticity are shown in Table 5. Among them,

[0120] Skin elasticity growth rate W% = (elasticity test value after application - elasticity test value before application) / elasticity test value before application * 100%.

[0121] Table 5. Skin elasticity test results

[0122] Test Group Week 0 Week 4 Elastic growth rate Example 1 0.64 0.92 43.75% Example 4 0.66 0.96 45.45% Example 5 0.68 0.96 41.18% Comparative Example 1 0.65 0.81 24.62% Comparative Example 8 0.64 0.85 32.81% Comparative Example 9 0.67 0.87 29.86% Comparative Example 10 0.62 0.83 33.87% Comparative Example 11 0.66 0.85 28.78%

[0123] As can be seen from Table 5, the compositions of Examples 1, 4 and 5 of the present application can achieve a skin elasticity growth rate of more than 40% after 4 weeks of use; while in Comparative Example 1, even though the components of the essence are the same, the skin elasticity growth rate is only 24% due to the use of traditional silk mask materials; and in other comparative examples, due to the use of different bioactive peptides, they have a certain effect on the growth of skin elasticity, but the effect is far less than that of Examples 1, 4 and 5. This shows that the bioactive peptides of specific amino acid sequences and the matrix materials obtained by specific processes can help enhance the promotion effect of the gel composition on the growth of skin elasticity, thereby exerting a better anti-aging effect.

[0124] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A firming and anti-wrinkle gel composition with barrier repairing effect, characterized in that: It is formed by soaking the matrix material in a serum; The matrix material is obtained by cross-linking carboxymethyl chitosan and rosmarinic acid to form a water-absorbing gel matrix, and then mixing the water-absorbing gel matrix with a water-soluble modified polysaccharide and performing electrostatic spinning; The essence comprises: 0.5-3.5wt% of animal placenta protein, 0.3-1.5wt% of bioactive peptides, 0.5-3% of hydrogenated castor oil, 0.1-4% of vitamin E, 0.2-0.5% of glycerol glucoside, 1-5% of glycerol, 0.1-4% of hyaluronic acid, 0.5-0.7% of carbomer, 0.01-0.05% of arginine, 0.1-1% of phenoxyethanol, 0.01-0.5% of EDTA-2Na, and the balance is deionized water.

2. The firming and anti-wrinkle gel composition with barrier repairing effect according to claim 1, characterized in that: The bioactive peptide includes at least one of PEP-129, PEP-383 and PEP-518; The amino acid sequence of PEP-129 is: Leu-Asp-Glu-Glu-Asn-Gly-Glu-Leu; The amino acid sequence of PEP-518 is: Gly-Asp-Pro-Glu-Arg-Phe-Tyr-Cys; The amino acid sequence of PEP-383 is: Cys-Leu-Gln-Pro-Glu-Thr-Gly-Glu-Tyr-Arg-Cys.

3. The firming and anti-wrinkle gel composition with barrier repairing effect according to claim 1, characterized in that: The preparation method of the matrix material comprises: The carboxymethyl chitosan is mixed with rosmarinic acid and water, and cross-linked at 135-145°C for 2-5 hours to obtain a water-absorbing gel matrix; The water-absorbent gel matrix is ​​mixed with the water-soluble modified polysaccharide and water to form a spinning solution, and the spinning solution is subjected to electrostatic spinning to obtain a matrix material.

4. The firming and anti-wrinkle gel composition with barrier repairing effect according to claim 3, characterized in that: The water-soluble modified polysaccharide is obtained by blending and modifying pullulan polysaccharide and bletilla striata polysaccharide in a mass ratio of 8-10:

1.

5. The firming and anti-wrinkle gel composition with barrier repairing effect according to claim 4, characterized in that: The mass ratio of the water-absorbent gel matrix to the water-soluble modified polysaccharide is 1:5-7, and the concentration of the spinning solution is 15-17%.

6. The firming and anti-wrinkle gel composition with barrier repairing effect according to claim 3, characterized in that: In the process of preparing the water-absorbing gel matrix, the mass ratio of the carboxymethyl chitosan to rosmarinic acid is 450-550:1; the mass volume ratio of the carboxymethyl chitosan to water is (0.9-1.1):

20.

7. The firming and anti-wrinkle gel composition with barrier repairing effect according to claim 3, characterized in that: In the electrospinning process, the spinning voltage is 28-30 KV, the receiving distance is 22-24 cm, and the extrusion rate is 0.4-0.6 ml / h.

8. A method for preparing the gel composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: Disperse glycerin, hyaluronic acid and EDTA-2Na into deionized water, then add vitamin E, glyceryl glucoside, hydrogenated castor oil, bioactive peptides and animal placenta protein, heat and dissolve, add arginine to adjust the pH to 5.5-6.5, finally add carbomer and phenoxyethanol, filter and obtain an essence; The essence solution is mixed with the matrix material and sterilized.

9. The method for preparing the gel composition according to claim 8, characterized in that: The mass volume ratio of the matrix material to the essence is 4-6:25.

Citation Information

Patent Citations

  • Natural anti-aging mask and preparation method and application thereof

    CN110974755A

  • Polypeptide for specifically promoting Nrf2 gene expression and application thereof

    CN117964694A